Antifungal activity of the repurposed drug disulfiram against Cryptococcus neoformans - Peng, Min; Zhang, Chen; Duan, Yuan-Yuan; Liu, Hai-Bo; Peng, Xin-Yuan; Wei, Qian; Chen, Qi-Ying; Sang, Hong; Kong, Qing-Tao (Frontiers in Pharmacology, 2024)
Fungal infections have become clinically challenging owing to the emergence of drug resistance in invasive fungi and the rapid increase in the number of novel pathogens. The development of drug resistance further restricts the use of antifungal agents. Therefore, there is an urgent need to identify alternative treatments for Cryptococcus neoformans (C. neoformans). Disulfiram (DSF) has a good human safety profile and promising applications as an antiviral, antifungal, antiparasitic, and anticancer agent. However, the effect of DSF on Cryptococcus is yet to be thoroughly investigated. This study investigated the antifungal effects and the mechanism of action of DSF against C. neoformans to provide a new theoretical foundation for the treatment of Cryptococcal infections. In vitro studies demonstrated that DSF inhibited Cryptococcus growth at minimum inhibitory concentrations (MICs) ranging from 1.0 to 8.0 μg/mL. Combined antifungal effects have been observed for DSF with 5-fluorocytosine, amphotericin B, terbinafine, or ketoconazole. DSF exerts significant protective effects and synergistic effects combined with 5-FU for Galleria mellonella infected with C. neoformans. Mechanistic investigations showed that DSF dosedependently inhibited melanin, urease, acetaldehyde dehydrogenase, capsule and biofilm viability of C. neoformans. Further studies indicated that DSF affected C. neoformans by interfering with multiple biological pathways, including replication, metabolism, membrane transport, and biological enzyme activity. Potentially essential targets of these pathways include acetaldehyde dehydrogenase, catalase, ATP-binding cassette transporter (ABC transporter), and iron-sulfur cluster transporter. These findings provide novel insights into the application of DSF and contribute to the understanding of its mechanisms of action in C. neoformans.